Optimizing conditions to improve polyphenol content and screening antioxidant capacity with DNA protection activity of Perilla frutescens - Ngoc Thien Kim Nguyen; Huynh Anh Vu Truong; Hoang Khue Tu Nguyen (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
Polyphenols are among the natural antioxidants that have been exploited in recent years for their safe and effective ability against oxidative stress. This project aimed to optimize 3 factor-conditions affecting total polyphenols extracted from Perilla frutescens (L.) Britt as well as DNA protection activity of polyphenols for applications in the fields of dietary supplements, pharmaceuticals, and health care. All extracts contained phenolic compounds and exhibited good antioxidant ability through a ferric reducing antioxidant power assay. The total polyphenolic compounds varied from 6.056 ± 0.08 to 9.630 ± 0.127 mg of gallic acid equivalents (GAE) per 1 g dry weight (dw). The highest phenolic content yield was extracted at 70°C for 60 minutes at a pH of 7.0. However, a sample with the highest polyphenol content had a lower residual DNA concentration than the extract (55°C, 60 min, and pH 6.0) with the greatest reducing power. The result of the DNA protection assay also indicated that the extraction concentration and pH condition had a significant effect on preventing DNA from being damaged by free radicals. The study found the conditions for improving polyphenol in the extraction of P. frutescens (L.) Britt with the aid of Box-Behnken Design. This research also proposed that P. frutescens (L.) Britt is a good source showing DNA protection and antioxidant activity for healthcare.